The Influence of Promotion Mix on the Purchase Decision of Participants of the Grand Reunion Stand of the Medan State Polytechnic Grand Reunion Event - Stevanus, Rico; Nursiah, Nursiah (CV. Civiliza Publishing, 2025)
Purchasing decision is the process by which a consumer decides to buy a product or service. Purchasing decisions can be influenced by several factors including advertising, personal sales, and public relations, which are some of the parts of the promotional mix. The purpose of this study is to determine the influence of the promotional mix on the purchase decision of participants of the Medan State Polytechnic (Polmed) Grand Reunion Stand Event. Data collection through a survey by distributing questionnaires to MSMEs who are participants in the bazaar stand at the Medan State Polytechnic Grand Reunion event. The number of population and samples in this study is as many as 45 bazaar stand participants. Data collection is through questionnaires and literature studies, while to test the quality of data, validity and reliability tests are carried out. To determine the influence of advertising, personal sales, and public relations on purchase decisions, multiple linear regression tests were performed. The results of the research obtained by advertising have a positive and significant effect on purchase decisions. This shows that the ads made by the committee affect the interest of potential consumers, which ultimately drives purchase decisions. Meanwhile, personal sales have a positive but not significant effect on purchasing decisions. This influence is not strong enough to significantly influence consumer decisions in purchasing decisions. Public relations has a positive and significant influence on the decision to purchase the Medan State Polytechnic Bazaar (Polmed) Stand Event. Advertising, personal sales, and public relations are explained to affect purchasing decisions by 62.3%, while the rest are influenced by other variables.